2013
DOI: 10.1117/12.2028902
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of index of refraction changes in chalcogenide glasses during molding processes

Abstract: Precision glass molding has a well-documented effect of a decrease in the index of refraction of the glass during the molding process. This index drop has such significant value that optical designs for molded lenses must take into account the index drop to accurately determine the optical performance of the final lens. Widespread adoption of chalcogenide glasses for molded infrared optics has raised a series of questions as to the behavior of these glasses under molding conditions. This paper will investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The refractive index drop is about 0.0193 at cooling rate of 360 K/h, and the calculated results are considerably comparable with other similar chalcogenide glasses . For example, the refractive index drop of As 40 Se 60 studied in Deegan et al .…”
Section: Dependence Of Refractive Index Change On Cooling Ratesupporting
confidence: 84%
See 1 more Smart Citation
“…The refractive index drop is about 0.0193 at cooling rate of 360 K/h, and the calculated results are considerably comparable with other similar chalcogenide glasses . For example, the refractive index drop of As 40 Se 60 studied in Deegan et al .…”
Section: Dependence Of Refractive Index Change On Cooling Ratesupporting
confidence: 84%
“…Refractive indices of chalcogenide glasses experience similar changes in molding. For example, the refractive index changes of several chalcogenide glasses were experimentally measured in references, and the results showed that the refractive index drop for NRL‐9 can be as high as 0.045 . To fully understand the material behaviors and property changes of As 2 S 3 in compression molding process, refractive index changes of As 2 S 3 glass at different cooling rates were calculated based on the structural relaxation data reported previously …”
Section: Introductionmentioning
confidence: 99%
“…This technology involves the well-documented effect of a decrease in the refraction index of the glass during the moulding process. The change in refraction index has such a significant influence on the optical design that it should be taken into account to accurately determine the optical performance of the final lens, as shown for As 2 Se 3 and Ge 28 Sb 12 Se 60 optical glasses [36]. Both viscosity and structural relaxation behaviour in undercooled liquid certainly play an essential role in this respect.…”
Section: Applications Of Chalcogenide Amorphous Materialsmentioning
confidence: 99%
“…8,9 However, additional glass treatment at temperatures close to the glass transition temperature T g can lead to such problems as phase transformations, the appearance of mechanical stresses in the volume of the material, 10 a change in the refractive index of the glass. 11 The temperature profile of the heating element and the speed of the extruded fiber in the temperature field made by the heater largely determine the optical and mechanical properties of the resulting optical fiber. Another important component of the extrusion process is to ensure the uniformity of the fiber diameter along the length, which is also determined by the dynamics of cooling of the extruded fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion could be used for both perform and fiber fabrication 8,9 . However, additional glass treatment at temperatures close to the glass transition temperature T g can lead to such problems as phase transformations, the appearance of mechanical stresses in the volume of the material, 10 a change in the refractive index of the glass 11 . The temperature profile of the heating element and the speed of the extruded fiber in the temperature field made by the heater largely determine the optical and mechanical properties of the resulting optical fiber.…”
Section: Introductionmentioning
confidence: 99%